Global Crisis of LGBTQ+ Homeless Youth: A Call for Inclusive Policies and Accurate Data - Renderos, Hugo; Alleyne, Antonio (International Journal on Homelessness, 2026)
Homelessness is not only a topic that significantly needs to be unpacked in the United States (US) but an issue for global society: a pressing humanitarian issue with disproportionate rates of housing instability rooted in systemic discrimination, family rejection, and societal stigma. In the US alone, lesbian, gay, bisexual, transgender, queer, plus (LGBTQ+) youth’s likelihood of experiencing homelessness doubles when compared to their heterosexual peers. Only transgender and nonbinary youth face higher risks, according to recent studies. In the European Union, studies also suggest that LGBTQ+ youth are overrepresented among homeless populations, comprising up to 30% of the total (Fraser et al., 2019). These displacements are often driven by familial rejection, religious convictions, and societal homophobia, as well as structural factors such as poverty and the lack of supportive housing systems. This article explores the service provisions model of Casa 1 and the experiences of youth in countries struggling with their development agenda, compounded by the experiences of homelessness as an identified member of the LGBTQ+ youth community. Within the Latin American community, ranked highest, Brazil’s LGBTQ+ youth make up 30-40% of the homeless youth (Brazilian Association of Homotransaffective Families [ABRAFH], 2020), and Argentina reports 30-35% due to family violence (Buenos Aires City Government , 2019).